Analisis Regresi dengan Variabel Dummy pada Faktor Risiko Diabetes Mellitus Tipe 2 - Diana, Putri; Murni, Dewi (Journal of Mathematics UNP, 2023)
Diabetes Mellitus is a metabolic disorder that occurs when blood glucose levels exceed normal limits, that is 126 mg/dl. If high blood sugar levels are not controlled, this can lead to complications and even death. This study aims to create a multiple linear regression model and discover the factors that affect blood sugar that it raises the risk of diabetes mellitus. This research using secondary data obtained from the Dadok Tunggul Hitam Health Center. The samples used were 286 samples. Blood sugar level is the dependent variabel, and the independent variabels are age, abdominal circumference, body mass index, and gender. By using multiple linear regression analysis using one dummy variabel, obtaines models:Y’ = 0,000157 -0,000001 X1 - 0,000001 X3 + 0,000013 DThe model shows that with α=5%, the variable that significantly affect blood sugar are gender, age, and body mass index.